Resolution of vaccinia virus DNA concatemer junctions requires late-gene expression. - Merchlinsky, M (1989)
Vaccinia virus replicates in the cytoplasm of infected cells, generating transient replicative intermediates containing the DNA for the terminal sequences as concatemeric junctions. The processing of the terminal sequences for a series of vaccinia virus conditional lethal mutants at the nonpermissive temperature was analyzed by restriction enzyme digestion and Southern blot hybridization of DNA isolated from infected cells. Three phenotypes were observed: DNA replication negative (Rep-), DNA replication positive but concatemer resolution negative (Rep+ Res-), and DNA replication positive and concatemer resolution positive (Rep+ Res+). Interestingly, all six Rep+ Res- mutants from separate complementation groups were defective in late protein synthesis. Isatin beta-thiosemicarbazone, a drug that blocks late protein synthesis, also prevented resolution of concatemers. Orthogonal field gel electrophoresis of the DNA generated by the late defective mutants revealed a distribution of linear genome multimers. The multimers were processed into mature monomers after a shift to the permissive temperature in the presence of cytosine arabinoside for all the Rep+ Res- mutants except ts22, an irreversible mutant which cleaves RNA late in infection (R.F. Pacha and R.C. Condit, J. Virol. 56:395-403, 1985). Genome formation can be divided into two stages: DNA replication, which generates concatemers, and resolution, which processes concatemers into monomers with hairpin termini. Early viral genes are required for the former, and late viral genes are required for the latter.